POLA PENEMUAN INFORMASI (INFORMATION SEEKING BEHAVIOR) DALAM UPAYA PENGEMBANGAN USAHA PADA KALANGAN PELAKU USAHA MIKRO KECIL DAN MENENGAH DI DESA SERANG KECAMATAN PANGGUNGREJO KABUPATEN BLITAR - Aprillia Novi Saputri; Prisca Budi Juvitasari (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2024)
The need for information in efforts to develop micro, small and medium enterprises encourages information seeking behavior among MSME business actors. This research aims to determine the information seeking behavior by MSME business actors in the Serang village area, Panggungrejo subdistrict, Blitar district to meet information needs for business development, as well as to find out the obstacles faced by MSME business actors in finding information and how to overcome them. The research method used is descriptive research with a qualitative approach. The data collection techniques used were open interviews with 6 informants, observation and study of literature. Data analysis techniques use data reduction, data presentation and drawing conclusions. The research results show that there are eight stages of information seeking behavior carried out by coffee and chips MSME business actors, including starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. The information they get is from articles or journals, social media, friends, relatives, and training. Meanwhile, the obstacle faced is that there are some people who do not want to share the information they have. To overcome this obstacle, there are two things that can be done, namely by looking for other sources of information and inviting the person to have frequent discussions and be good friends so that they themselves provide the information needed.